A survey about prophage induction ability in Escherichia coli K-12(λ) by ethnic medicinal plants of Kohgiluyeh va Boyerahmad, Iran - M. Hamzeloo-Moghadam; B. Eslami Tehrani; A. Pirani; A. Hassanpour; S. Esmaeili (Iranian Society of Pharmacognosy, 2014)
Background and objectives: There is a growing trend towards investigating natural products as sources of compounds with biological effects and many researches have been carried out in order to find effective medications against many diseases. Cancer is no exception and studies focusing on evaluating the effects of different materials on DNA, give valuable information in cancer researches and carcinogenicity studies; thus the present study was focused on evaluating the impact of medicinal plants from  Kohgiluyeh va Boyerahmad province, Iran on DNA. Methods: Thirty five plant species collected have been investigated for prophage induction ability in Escherichia coli K-12(λ)throughinductest. Results:The assay demonstrated that 8 plants were able to affect DNA. Conclusion: The results confirm the role of natural resources for biologic effects and what's more, potential drug candidates in new drug discovery.